Cyber DoS attack based security simulator for VANET - Muntadher Naeem Yasir; Muayad Sadik Croock (International Journal of Electrical and Computer Engineering (IJECE), 2020)
At the late years, researches focused on the cyber Denial of Service (DoS) attacks in the Vehicle Ad hoc Networks (VANETS). This is due to high importance of ensuring the save receiving of information in terms of Vehicle to Vehicle (V2V), Vehicle to Infrastructure (V2I) and Vehicle to Road Side Unit (V2R). In this paper, a cyber-security system is proposed to detect and block the DoS attacks in VANET. In addition, a simulator for VENAT based on lightweight authentication and key exchange is presented to simulate the network performance and attacks. The proposed system consists of three phases: registration, authentication as well as communications and DoS attack detection. These phases improve the system ability to detect the attacks in efficient way. Each phase working is based in a proposed related algorithm under the guidance of lightweight protocol. In order to test the proposed system, a prototype is considered includes six cars and we adopt police cars due to high importance of exchanged information. Different case studies have been considered to evaluate the proposed system and the obtained results show a high efficiency of performance in terms of information exchange and attack detection.